[Brzeźno, plaża] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia fragment plaży w Brzeźnie. Widok z tarasu Hali Brzegowej w kierunku Sopotu, ok. 1910 r.